Evaluating the implementation of the National Primary Health Care Development Agency (NPHCDA) gateway for the Basic Healthcare Provision Fund (BHCPF) across six Northern states in Nigeria - Uchenna Igbokwe; Raihanah Ibrahim; Muyi Aina; Musa Umar; Muhammed Salihu; Efosa Omoregie; Firdausi Umar Sadiq; Benson Obonyo; Rilwanu Muhammad; Salisu Idris Isah; Natsah Joseph; Babagana Wakil; et al. (BMC, 2024)
Abstract Background This evaluation research utilized both qualitative and quantitative methods to assess the implementation of the National Primary Health Care Development Agency (NPHCDA) gateway of the Basic Health Care Provision Fund (BHCPF) across six states in Northern Nigeria: Bauchi, Borno, Kaduna, Kano, Sokoto, and Yobe. Methods This was a mixed-method research that utilized longitudinal surveys and Key informant interviews to gather information about the implementation status of the BHCPF-NPHCDA gateway. Checklists were developed based on the BHCPF's national guidelines to gather quantitative data, while simple open-ended questionnaires were used to collect qualitative data from the state BHCPF Program Implementation Unit (PIU) focal persons as key informants. Results The result revealed that the NPHCDA had accredited these six states to use one Primary Health Care (PHC) facility in each political ward to implement the BHCPF. Factors that contributed to the success achieved in some states included the early completion of contingent start-up activities, well-established coordination structures, strong support from partners, and the availability of established financial management systems. However, the delays in the submission of quarterly business plans by the BHCPF facilities affected timely approval and fund disbursement. Other challenges included staff capacity gaps, inadequate human resources, and poor management and supervision from the state health agency teams. Conclusion There was suboptimal implementation of the BHCPF in at least one thematic area across all states. Therefore, actions such as government commitment for improved coordination, continuous capacity building, effective monitoring and evaluation, and targeted supportive supervision using innovative approaches should be undertaken to improve the program's implementation. In a broader setting, the insights from BHCPF implementation are valuable for LMICs, offering guidance on overcoming implementation challenges associated with PHC financing. This research provides a resource for enhancing healthcare financing strategies in similar contexts.